2019
DOI: 10.18311/ijmds/2019/23418
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Prescribing Pattern in Patients of Hypertension

Abstract: Introduction: Hypertension is a multi-factorial and complex disease that has both environmental and genetic determinants. It is the single most significant risk factor for heart diseases and kidney diseases. Hypertension is a leading contributor to global burden of morbidity and mortality. It is considered as a silent killer because most of the time it is asymptomatic and goes undetected. Hence, hypertensive patients should be prescribed properly. Objectives: To evaluate the prescribing pattern of anti-hyperte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 10 publications
3
4
1
Order By: Relevance
“…In our study we observed BB+ ARB are highly used it occupies 19.73% and complies with Haq et al (2019) and (Singla et al, 2018) (47.46%) but (4.81%) according to (Romday et al, 2016) entirely contradict to our observation. BB+CCB (17.27%) and in (Singla et al, 2018) (4.13%) but (Romday et al, 2016) indicates 12.04% similar to our observations.…”
Section: Dual Therapycontrasting
confidence: 92%
See 4 more Smart Citations
“…In our study we observed BB+ ARB are highly used it occupies 19.73% and complies with Haq et al (2019) and (Singla et al, 2018) (47.46%) but (4.81%) according to (Romday et al, 2016) entirely contradict to our observation. BB+CCB (17.27%) and in (Singla et al, 2018) (4.13%) but (Romday et al, 2016) indicates 12.04% similar to our observations.…”
Section: Dual Therapycontrasting
confidence: 92%
“…ARB (31.78%), CCB(9.15%), DI(4.56%), ACEI (4.56%). In our study we observed BB (61.91%) , ARB (13.76%), CCB (12.69%), DI (5.69%), ACEI (3.17%) and complies with (Haq et al, 2019) α +β blockers (2.78%). According to (Singla et al, 2018) ARB (45.47%), BB(9.09%), CCB(22.75%), ACEI(20.64%), DI (2.05%).…”
Section: Monotherapysupporting
confidence: 70%
See 3 more Smart Citations